In vivo evaluation of three biomarkers in the mosquitofish (Gambusia yucatana) exposed to pesticides - Rendon-Von Osten, J.
In this study, the acute toxicity and the in vivo effects of commercial chlorpyrifos, carbofuran and glyphosate formulations on cholinesterase (ChE), glutathione S-transferase (GST) and lactate dehydrogenase (LDH) activities of the mosquitofish (Gambusia yucatana) were investigated. In a first phase of the study, head and muscle ChE were characterized with different substrates (acetylthiocholine iodide, s-butyrylthiocholine iodide and propionylthiocholine iodide) and the selective inhibitors eserine hemisulfate, 1,5-bis(4-allyldimethylammoniumphenyl)-pentan-3-one dibromide (BW284C51), and NN'-diisopropylphosphorodiamic acid (iso-OMPA). The results obtained suggest that the enzyme present in both head and muscle of G. yucatana is mainly acetyleholinesterase (AChE). Acute toxicity was evaluated by exposing fish to several concentrations of single pesticides and of a mixture of chlorpyrifos/glyphosate. LC50 values were detemined after 96 h of exposure, except in the case of carbofuran for which LC50 was calculated after 24 h since almost all the fish died within this period. LC50 values were 0.085mg/l for chlorpyrifos, 17.79mg/l for glyphosate, 0.636mg/l for carbofuran and 0.011 mg/l for the chlorpyrifos/glyphosate mixture. A Toxic Unit approach was used to compare the toxicity of chlorpyrifos and glyphosate when occurring in a mixture, with their toxicities as single compounds. Synergistic effects of chlorpyrifos and glyphosate when present in a mixture were found. At the end of each bioassay (24 h for carbofuran, 96 for the other substances/mixture), effects on biomarkers were analyzed. Muscle LDH activity was not altered by any of the three pesticides tested. Gill GST activity was significantly inhibited (40%) by carbofuran after 24 h of exposure to concentrations equal or higher than 0.06mg/l. ChE muscle and head activity were significantly inhibited (50% and 30%, respectively) by carbofuran at concentrations equal or higher than 0.25mg/l. Chlorpyrifos induced a significant inhibition of both muscle and head ChE (80% and 50%, respectively) after 96 h of exposure to concentrations equal or higher than 0.05mg/l. Carbofuran did not induce significant alterations of fish ChE. The ChE EC50 determined for chlorpyrifos/glyphosate mixture (0.070mg/l) was higher than the correspondent value calculated for chlorpyrifos alone (0.011 mg/l) suggesting an antagonistic effect of glyphosate on ChE inhibition by chlorpyrifos. ChE activity of G. yucatana seems to be a good biomarker to diagnose the exposure of wild populations of this species exposed to anticholinesterase pesticides. (C) 2004 Elsevier Ltd. All rights reserved.